INDEKS PEMBANGUNAN MANUSIA PADA KABUPATEN/KOTA DI SUMATERA UTARA: EFEK MEDIASI BELANJA MODAL - Oktaviani Pekiningrum; Puji Wibowo (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
Fiscal decentralization gives local governments the authority to use revenues to finance local expenditure, one of which is expenditures intended to improve the quality of human development. This study aims to analyze the effect of Local Own Source Revenue (PAD), Special Allocation Funds (DAK), and Surplus of Budget Financing (SiLPA) on the Human Development Index (IPM) through capital expenditure on districts/cities in North Sumatra. This study uses panel data consisting of time series data for 2015-2019 and cross section data for 33 districts/cities in North Sumatra. Hypothesis testing is done by multiple linear regression and path analysis. The results of the study proved that DAK and SiLPA have a positive impact on capital expenditures, while PAD has no impact on capital expenditures. Meanwhile, PAD and DAK directly have a significant positive effect on HDI, while SiLPA has no effect on HDI. In addition, PAD, DAK, and SiLPA indirectly have no significant effect on HDI through capital expenditure.